The Older Adults With Rectal Cancer—Does Age Matter?: A Single-center Experience. (December 2020) - Shulman, Katerina; Musallam, Samar; Epelbaum, Ron; Haim, Nissim; Ben-Yosef, Rahamim; Kaidar-Person, Orit
Abstract : Objectives: Oncological treatments of older patients have many unresolved questions mainly because of the fact that these patients were not eligible to be included in most clinical trials. The aim of this study was to evaluate the treatment approach to localized rectal cancer in the older population, including complication rates and overall survival in patients treated with curative intent. Materials and Methods: A retrospective review of patients older than 80 years old (group A) who were treated for clinical stages II to III rectal cancer. The data collection included demographics, comorbidities, treatment protocols, adverse events, time of death, and a comparison with a group of patients aged 65 to 75 years (group B). Results: A total of 88 patients were included in the analysis (group A, 35; group B, 53). The groups were balanced with regards to sex, comorbidities, pretreatment albumin, and hemoglobin levels (for all categories P >0.05). More patients in group A (25%) received preoperative treatment as in-patients ( P =0.022) and were treated with radiation only ( P <0.0001) as the initial treatment approach. In group A, in 82% of patients the initial chemotherapy dose was reduced to 75% or less of the calculated dose compared with 7% in group B ( P <0.001). Discontinuation of chemotherapy was needed in 55% in group A and 31% in group B ( P =0.07). Median overall survival was 33 months in group A and 55 months in group B ( P =0.06), 5-year overall survival was 27% and 60%, respectively ( P =0.004). Conclusions: The age has a significant implication on preoperative treatment, chemotherapy dose, hospitalization rates, and survival.